EFEKTIVITAS MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN APLIKASI POWTOON - Nela Sari Yolanda; Niscaya Laia (STKIP Pesisir Selatan, 2023)
Learning media is one of the intermediaries used to convey messages from the teacher to students. In the world of education, learning media are known as intermediaries that are used to convey messages so that students understand the material delivered by the teacher to students so that the learning objectives are achieved. The function of the media was originally only known as a tool in teaching and learning activities that is providing visual experience in order to encourage learning motivation, clarify and facilitate complex concepts. This research aims to find out the effectiveness of mathematics learning media using the Powtoon application, by looking at student learning outcomes Between classes that use learning media using powtoon applications with classes that do not use learning media using the powtoon application. The type of research used is Research & Development, data collection techniques in this study are primary data, namely data obtained from student learning outcomes tests. The data analysis technique used in this study is a quantitative technique. Based on the results of the analysis shows that the learning media developed has been effectively seen from the learning outcomes of students to increase after the use of learning media using Powtoon applications.